Typical Consonant Acquisition by Children across Dialects in Vietnam - Phạm, Ben; Phạm, Hang; Phạm, Van; Minh Tran, Thanh Thi; Hoang, Nho; Bui, Lam; Chung, Luu Thi; Pham, Yen Hai Thi; Dao, Thuy; Pham, Linh Thuy (Forum for Linguistic Studies, 2024)
Information about typical consonant acquisition holds a key position in the practice of speech-language therapy. The purpose of this review article was to describe the typical age of acquisition of consonants produced by children across dialects in Vietnam. A review was undertaken of seven studies reporting consonant acquisition by 1,631 children living in Vietnam. Data were extracted to describe methodological aspects and the age of acquisition of individual Vietnamese consonants. Combining data from the seven studies reveals that most Vietnamese consonants are acquired by age 5. Ordered by the mean age of acquisition at the 90% criterion, Vietnamese children acquired three initial consonants (/m-, b-, ʔ-/), one final consonant (/-m/), and two final semivowels (/-w, -j/) by 2;0-2;11 (years; months); six initial consonants (/c-, k-, n-, ɲ-, f-, h-/) and seven final consonants (/-p, -t, -k, -kp, -n, -ŋ, -ŋ-) by 3;0-3;11; six initial consonants (/d-, t-, ŋ-, s-, ɣ-, l-/) by 4;0-4;11; four initial consonants (/x-, t̪ʰ-, v-, ʈ-/) by 5;0-5;11; and four initial consonants (/ʂ-, p-, ʐ-, z-/) and two final consonants (/-c, -ɲ/) by 6;0-6;11. Vietnamese final consonants were acquired earlier than initial consonants. Plosives and nasals were acquired earlier than fricatives. Most labials were acquired earlier than velars and retroflexes. These findings on Vietnamese consonant acquisition are similar to those in English and other global cross-linguistic studies, which show that children acquire most consonants by age 5. This information is essential for speech and language therapists and other related professionals working with Vietnamese-speaking children to apply in their clinical decision-making.